Ferritic stainless steel sheet for battery part and method for manufacturing the same and battery part and method for manufacturing the same

A ferritic stainless steel sheet with controlled composition and manufacturing processes addresses deep drawing challenges, enhancing workability and suppressing cracks in battery parts like square cases, ensuring high reliability and productivity.

JP2025006577APending Publication Date: 2025-01-17NIPPON STEEL STAINLESS STEEL CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023107460
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Ferritic stainless steel sheets face challenges in deep drawing due to low workability and susceptibility to cracking, particularly in manufacturing battery parts like square cases for lithium-ion secondary batteries, which affect reliability and productivity.

Method used

A ferritic stainless steel sheet with controlled composition, average Lankford value, 0.2% proof stress, surface roughness, and specific manufacturing processes including hot rolling, annealing, and temper rolling to enhance deep drawing workability and suppress cracking.

Benefits of technology

The solution provides a ferritic stainless steel sheet with excellent deep drawing properties, reducing the occurrence of various cracks and ensuring high reliability of battery components, particularly in square cases, without the need for intermediate annealing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025006577000007
    Figure 2025006577000007
  • Figure 2025006577000008
    Figure 2025006577000008
  • Figure 2025006577000009
    Figure 2025006577000009
Patent Text Reader

Abstract

To provide a ferritic stainless steel sheet for a battery part having excellent deep drawability and capable suppressing various types of cracking.SOLUTION: There is provided a ferritic stainless steel sheet for a battery part which comprises, on a mass basis, C: 0.001 to 0.020%, N: 0.001 to 0.020%, Si: 0.01 to 0.60%, Mn: 0.01 to 0.70%, P: 0.001 to 0.050%, S: 0.0001 to 0.0014%, Cr: 9.5 to 18.5%, Ni: 0.001 to 0.700%, Cu: 0.001 to 1.200%, Ti: 0.03 to 0.27%, Nb: 0.001 to 0.200%, Al: 0.003 to 0.180% and the balance Fe with impurities. The ferritic stainless steel sheet for a battery part has an average Lankford value of 1.20 or higher, a 0.2% proof stress of 200 to 290 MPa, a surface arithmetic mean roughness Ra of 0.01 to 1.00 μm, a surface maximum height roughness Rz of 0.10 to 5.00 μm, and a ratio Rz / Ra of the maximum height roughness Rz to the arithmetic mean roughness Ra is 2.0 to 15.0 and satisfies the following expression (1). 7.7×(C+N)≤Ti+Nb≤0.340 (1) In the expression, each element symbol represents the content (mass %) of each element.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a ferritic stainless steel sheet for battery components and a manufacturing method thereof, as well as a battery component and a manufacturing method thereof. [Background technology]

[0002] Among various types of batteries, lithium-ion secondary batteries have been used as power sources for mobile phones, smartphones, notebook computers, and other devices due to their high voltage, light weight, high energy density, and high power density. On the other hand, greenhouse gases (CO 2 ) reduction and oil resource issues, 2 Due to regulations on exhaust gas emissions and fuel efficiency, vehicles such as hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), electric vehicles (EVs), and fuel cell vehicles (FCVs) have been developed, and lithium-ion secondary batteries are used as their power source.

[0003] Lithium-ion secondary batteries for vehicles are classified into cylindrical, prismatic, laminated, etc., depending on their shape, but the prismatic and laminated types are widely used from the viewpoint of space saving. In a prismatic lithium-ion secondary battery, a laminate in which a separator is disposed between a positive electrode and a negative electrode is housed in a prismatic case mainly made of aluminum.

[0004] Lithium ion secondary batteries for vehicles are required to have increased battery capacity, energy density, and power density in order to extend the driving range, so the reliability of the prismatic case is also a very important issue. For this reason, evaluations are performed on the prismatic case in cases where the positive and negative electrodes are short-circuited internally or externally by nail penetration tests, crash tests, external short tests, etc., or where the non-aqueous electrolyte reacts and becomes abnormally high due to a sudden increase in temperature. However, in the case of a prismatic case made of aluminum, the high-temperature strength and melting point are low, so the evaluation results are often insufficient. In particular, in the case of large-capacity lithium ion secondary batteries, prismatic cases made of stainless steel are more reliable than prismatic cases made of aluminum, and are therefore used in some cases.

[0005] In order to increase the energy density, the shape of the square case is such that the height H is large relative to the width W, and the radius of curvature R of the corners is as small as possible. When manufacturing a square case of this shape by deep drawing of a stainless steel sheet, there are problems with workability. For example, austenitic stainless steel sheets such as SUS304 are generally excellent in workability, but when processing into a square case of the above shape, intermediate annealing is required during the deep drawing process due to concerns about age cracking at the corners. In addition, austenitic stainless steel sheets also contain a large amount of Ni, so the processing cost and material cost are high. On the other hand, ferritic stainless steel sheets contain a small amount of Ni (or no Ni), there is little concern about age cracking, and intermediate annealing can be omitted, which is advantageous in terms of cost.

[0006] In ferritic stainless steel sheets, deep drawability can be improved by minimizing C and N and stabilizing them with Ti, but improving deep drawability tends to reduce strength. Excessively low strength can easily cause cracks called wall breaks in deep-drawn products with asymmetric shapes such as square tubes, while increasing strength can easily cause secondary cracks and micro brittle cracks in corners.

[0007] Furthermore, as a technique for manufacturing square cases from ferritic stainless steel sheets, Patent Document 1 proposes a method of cooling the punch, heating the die and sheet holder, and setting the gap between the punch and the die smaller than the sheet thickness in the previous process to perform redrawing and ironing. However, this method has problems with productivity, and it is practically difficult to use it for manufacturing square cases that are expected to be mass-produced. Although the above description has focused on the rectangular case of a lithium ion secondary battery, the same problem exists in various battery components manufactured by deep drawing. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2009-113059 A Summary of the Invention [Problem to be solved by the invention]

[0009] The present invention has been made to solve the above-mentioned problems, and aims to provide a ferritic stainless steel sheet for battery components that has excellent deep drawing workability and can suppress the occurrence of various cracks, and a manufacturing method thereof. Another object of the present invention is to provide a highly reliable battery component and a method for manufacturing the same. [Means for solving the problem]

[0010] The present inventors have conducted extensive research into ferritic stainless steel sheets and found that the above problems can be solved by controlling the composition, average Lankford value, 0.2% yield strength, arithmetic mean surface roughness Ra, maximum height roughness Rz, and the ratio of Rz / Ra. They also found that a ferritic stainless steel sheet having such characteristics can be obtained by controlling the conditions of the hot rolling process, the annealing process, and the temper rolling process. The present invention was completed based on these findings.

[0011] That is, the present invention provides a steel sheet comprising, on a mass basis, 0.001-0.020% C, 0.001-0.020% N, 0.01-0.60% Si, 0.01-0.70% Mn, 0.001-0.050% P, 0.0001-0.0014% S, 9.5-18.5% Cr, 0.001-0.700% Ni, 0.001-1.200% Cu, 0.03-0.27% Ti, 0.001-0.200% Nb, and 0.003-0.180% Al, with the remainder being Fe and impurities; an average Lankford value of 1.20 or more, a 0.2% yield strength of 200 to 290 MPa, an arithmetic mean roughness Ra of the surface of 0.01 to 1.00 μm, a maximum height roughness Rz of the surface of 0.10 to 5.00 μm, and a ratio Rz / Ra of the maximum height roughness Rz to the arithmetic mean roughness Ra of 2.0 to 15.0, A ferritic stainless steel sheet for battery components that satisfies the following formula (1). 7.7×(C+N)≦Ti+Nb≦0.340 (1) In the formula, each element symbol represents the content (mass %) of each element.

[0012] The present invention also relates to a hot rolling process in which a stainless steel containing, by mass, 0.001-0.020% C, 0.001-0.020% N, 0.01-0.60% Si, 0.01-0.70% Mn, 0.001-0.050% P, 0.0001-0.0014% S, 9.5-18.5% Cr, 0.001-0.700% Ni, 0.001-1.200% Cu, 0.03-0.27% Ti, 0.001-0.200% Nb, 0.003-0.180% Al, with the balance being Fe and impurities, is heated to a heating temperature of 1100-1300°C for 30-240 minutes in an atmosphere containing 10-30 volume% water vapor, and hot rolled; a cold rolling step of cold rolling the hot-rolled sheet obtained in the hot rolling step; An annealing process in which the cold-rolled sheet obtained in the cold rolling process is annealed at a final annealing temperature of 850 to 1050 ° C.; a temper rolling process in which the annealed sheet obtained in the annealing process is temper rolled to an elongation rate of 0.03 to 1.00% under conditions that satisfy the following formula (2); The present invention relates to a method for producing a ferritic stainless steel sheet for battery components, comprising the steps of: -190≦50Cr+500Si-T+300A≦250 (2) In the formula, Cr and Si represent the Cr and Si contents (mass%), T represents the final annealing temperature (°C) in the annealing process, and A represents the elongation rate (%) in the temper rolling process.

[0013] The present invention also relates to a battery component comprising a deep-drawn product made of the above-mentioned ferritic stainless steel sheet for battery components. Furthermore, the present invention provides a method for producing a battery component, which comprises deep drawing the ferritic stainless steel sheet for battery components. Effect of the Invention

[0014] According to the present invention, it is possible to provide a ferritic stainless steel sheet for battery components which has excellent deep drawability and is capable of suppressing the occurrence of various cracks, and a method for producing the same. Furthermore, according to the present invention, it is possible to provide a highly reliable battery component and a manufacturing method thereof. [Brief description of the drawings]

[0015] [Figure 1A] FIG. 1 is a top view of a typical deep drawn product. [Figure 1B] FIG. 1 is a side view of a typical deep drawn product. [Diagram 2] FIG. 2 is a schematic diagram for explaining the manufacturing procedure of the rectangular case manufactured in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The following is a detailed description of the embodiments of the present invention. The present invention is not limited to the following embodiments, and it should be understood that modifications and improvements to the following embodiments, which are made based on the ordinary knowledge of those skilled in the art, fall within the scope of the present invention, without departing from the spirit of the present invention. In this specification, the "%" designation for components means "% by mass" unless otherwise specified.

[0017] (1) Ferritic stainless steel sheets for battery components A ferritic stainless steel sheet for battery components according to an embodiment of the present invention (hereinafter sometimes abbreviated as "ferritic stainless steel sheet") contains C: 0.001-0.020%, N: 0.001-0.020%, Si: 0.01-0.60%, Mn: 0.01-0.70%, P: 0.001-0.050%, S: 0.0001-0.0014%, Cr: 9.5-18.5%, Ni: 0.001-0.700%, Cu: 0.001-1.200%, Ti: 0.03-0.27%, Nb: 0.001-0.200%, Al: 0.003-0.180%, with the remainder being Fe and impurities.

[0018] Here, in this specification, "ferritic" means that the metal structure is mainly ferritic phase at room temperature. Therefore, "ferritic" also includes those that contain small amounts of phases other than ferritic phase (e.g., austenite phase, martensite phase, etc.). However, "ferritic" does not include a multi-phase structure of ferritic phase and austenite phase, a multi-phase structure of ferritic phase and martensite phase, or a multi-phase structure of ferritic phase, austenite phase, and martensite phase. In this specification, the term "impurities" refers to components that are mixed in due to various factors in raw materials such as ores and scraps and in the manufacturing process during industrial production of ferritic stainless steel sheets, and are acceptable within a range that does not adversely affect the present invention. For example, impurities include unavoidable impurities. An example of an impurity is O.

[0019] The ferritic stainless steel sheet according to the embodiment of the present invention may contain, as necessary, Mo: 0.01 to 2.50%, V: 0.01 to 0.50%, Zr: 0.01 to 0.50%, B: 0.0001 to 0.0050%, Ca: 0.0001 to 0.0100%, W: 0.01 to 2.50%, Sn: 0.01 to 0.50%, Co: 0.01 to 0.5 It may further contain one or more selected from the group consisting of 0%, Mg: 0.0001 to 0.0100%, Sb: 0.001 to 0.300%, REM: 0.001 to 0.500%, Ga: 0.0001 to 0.3000%, Ta: 0.001 to 1.000%, Hf: 0.001 to 1.000%, and Bi: 0.001 to 0.200%. Each component will be described in detail below.

[0020] <C:0.001~0.020%> If excessive C is added, the fixation of C becomes insufficient, resulting in a decrease in the average Lankford value and a tendency for cracks (α-fracture) to occur near the punch shoulder radius during deep drawing. In addition, if a large amount of C is added, the corrosion resistance decreases and the Ti content required to fix C also increases. Therefore, the C content is set to 0.020% or less, preferably 0.018% or less, and more preferably 0.015% or less. However, since an excessive reduction in C leads to an increase in refining costs, the C content is set to 0.001% or more, and preferably 0.002% or more.

[0021] <N:0.001~0.020%> As with C, excessive addition of N results in insufficient fixation of N, resulting in a decrease in the average Lankford value and a tendency for cracks (α fracture) to occur near the punch shoulder radius during deep drawing. In addition, addition of a large amount of N reduces corrosion resistance and increases the Ti content required to fix N. Therefore, the N content is set to 0.020% or less, preferably 0.018% or less, and more preferably 0.015% or less. However, since excessive reduction of N leads to an increase in refining costs, the N content is set to 0.001% or more, and preferably 0.002% or more.

[0022] <Si:0.01~0.60%> If a large amount of Si is added, vertical cracks are likely to occur at corners during deep drawing. Therefore, the Si content is set to 0.60% or less, preferably 0.55% or less, and more preferably 0.50% or less. On the other hand, an excessive reduction in Si content leads to a decrease in yield strength and makes wall breaks more likely to occur. Therefore, the Si content is set to 0.01% or more, preferably 0.02% or more.

[0023] <Mn:0.01~0.70%> As with Si, excessive addition of Mn makes it easier for vertical cracks to occur at corners during deep drawing. Therefore, the Mn content is set to 0.70% or less, preferably 0.60% or less, more preferably 0.55% or less, and even more preferably 0.40% or less. However, since excessive reduction of Mn leads to increased refining costs, the Mn content is set to 0.01% or more, preferably 0.05% or more.

[0024] <P:0.001~0.050%> P reduces workability by solid solution strengthening. In particular, excessive addition of P makes it easier for vertical cracks to occur at corners during deep drawing. Therefore, the P content is set to 0.050% or less, preferably 0.040% or less. However, excessive reduction of P increases steelmaking costs due to the selection of raw materials, etc., so the P content is set to 0.001% or more, preferably 0.005% or more.

[0025] <S:0.0001~0.0014%> If S is added in excess, vertical cracks are more likely to occur at corners during deep drawing, and inclusions etc. reduce corrosion resistance. Therefore, the S content is set to 0.0014% or less, preferably 0.0013% or less, and more preferably 0.0012% or less. However, since excessive reduction in S increases steelmaking costs due to the selection of raw materials etc., the S content is set to 0.0001% or more, preferably 0.0003% or more.

[0026] <Cr:9.5~18.5%> Cr is an element necessary to ensure corrosion resistance, which is a basic property of ferritic stainless steel sheets. However, if excessive Cr is added, vertical cracks are likely to occur at corners during deep drawing. Therefore, the Cr content is set to 18.5% or less, preferably less than 18.0%. On the other hand, excessive reduction in Cr reduces corrosion resistance and yield strength, making wall breaks more likely to occur. Therefore, the Cr content is set to 9.5% or more, preferably 9.8% or more, and more preferably 10.0% or more.

[0027] <Ni:0.001~0.700%> If Ni is added excessively, vertical cracks are likely to occur at corners during deep drawing. Therefore, the Ni content is set to 0.700% or less, preferably 0.600% or less, more preferably 0.550% or less, and even more preferably 0.400% or less. However, excessive reduction in Ni content leads to a decrease in yield strength and makes wall breaks more likely to occur. Therefore, the Ni content is set to 0.001% or more, preferably 0.002% or more.

[0028] <Cu:0.001~1.200%> If Cu is added excessively, vertical cracks are likely to occur at corners during deep drawing. Therefore, the Cu content is set to 1.200% or less, preferably 1.100% or less, and more preferably 0.400% or less. However, excessive reduction in Cu content leads to a decrease in yield strength and makes wall breaks more likely to occur. Therefore, the Cu content is set to 0.001% or more, and preferably 0.002% or more.

[0029] <Ti:0.03~0.27%> Excessive addition of Ti increases inclusions such as carbonitrides and oxides, which makes it easier for cracks (α-fracture) to occur near the punch shoulder radius during deep drawing. Therefore, the Ti content is set to 0.27% or less, preferably less than 0.25%. Also, if the amount of Ti added is too small, the fixation of C and N becomes insufficient, resulting in a decrease in the average Lankford value, which makes it easier for cracks (α-fracture) to occur near the punch shoulder radius during deep drawing. Therefore, the Ti content is set to 0.03% or more, preferably 0.05% or more, more preferably 0.10% or more.

[0030] <Nb:0.001~0.200%> When Nb is added in excess, the development of recrystallization and texture is delayed, resulting in a decrease in the average Lankford value, and cracks (α fracture) are likely to occur near the punch shoulder radius during deep drawing. Therefore, the Nb content is set to 0.200% or less, preferably 0.160% or less, and more preferably less than 0.100%. On the other hand, Nb is an element that combines with C and N to form precipitates and improve workability. Nb is also an element that improves corrosion resistance (especially the corrosion resistance of the welded part when welding). In order to obtain the effects of Nb, the Nb content is set to 0.001% or more, preferably 0.002% or more.

[0031] <Al:0.003~0.180%> When Al is added excessively, the amount of inclusions such as carbonitrides and oxides increases, and cracks (α-fracture) tend to occur near the punch shoulder radius during deep drawing. Therefore, the Al content is set to 0.180% or less, preferably 0.160% or less, and more preferably 0.150% or less. Also, if the amount of Al added is too small, the fixation of C and N becomes insufficient, resulting in a decrease in the average Lankford value, and cracks (α-fracture) tend to occur near the punch shoulder radius during deep drawing. Therefore, the Al content is set to 0.003% or more, and preferably 0.004% or more.

[0032] <Mo:0.01~2.50%> Like Cr, Mo is an element that is effective in ensuring corrosion resistance, which is a basic property of ferritic stainless steel sheets. To obtain the effects of Mo, the Mo content is set to 0.01% or more, preferably 0.05% or more. However, since excessive addition of Mo increases steelmaking costs and leads to increased strength and reduced elongation, the Mo content is set to 2.50% or less, preferably 2.30% or less, and more preferably 1.30% or less.

[0033] <V:0.01~0.50%、Zr:0.01~0.50%> V and Zr are elements that combine with C and N to suppress the formation of Cr carbonitrides. In order to obtain the effects of V and Zr, the V content and Zr content are each set to 0.01% or more, preferably 0.05% or more. However, since excessive addition of V and Zr reduces workability, the V content and Zr content are each set to 0.50% or less, preferably 0.40% or less, more preferably 0.20% or less.

[0034] <B:0.0001~0.0050%> B is an element that improves secondary workability and is effective in suppressing secondary work cracks during various processes after deep drawing. To obtain the effects of B, the B content is set to 0.0001% or more, preferably 0.0003% or more. However, since excessive addition of B leads to a decrease in elongation and average Lankford value, the B content is set to 0.0050% or less, preferably 0.0040% or less, and more preferably 0.0030% or less.

[0035] <Ca:0.0001~0.0100%> Ca is an element effective in fixing S and improving hot workability. To obtain the effect of Ca, the Ca content is set to 0.0001% or more, preferably 0.0002% or more. However, since excessive addition of Ca leads to a decrease in corrosion resistance, the Ca content is set to 0.0100% or less, preferably 0.0080% or less, and more preferably 0.0050% or less.

[0036] <W:0.01~2.50%> W is an element that improves corrosion resistance and also acts as a solid solution strengthening element. In order to obtain the effects of W, the W content is set to 0.01% or more, preferably 0.05% or more. However, since excessive addition of W leads to a decrease in workability and toughness, an increase in cost, etc., the W content is set to 2.50% or less, preferably 2.00% or less, more preferably 0.50% or less.

[0037] <Sn:0.01~0.50%> Sn is an element that enhances the repair ability of the passive film of the ferritic stainless steel sheet and enhances the corrosion resistance. To obtain the effect of Sn, the Sn content is set to 0.01% or more, preferably 0.02% or more. However, since excessive addition of Sn leads to an increase in strength and a decrease in ductility, the Sn content is set to 0.50% or less, preferably 0.40% or less, and more preferably 0.30% or less.

[0038] <Co:0.01~0.50%> Co is an element that contributes to improving high-temperature strength. In order to obtain the effects of Co, the Co content is set to 0.01% or more, preferably 0.03% or more. However, since excessive addition of Co leads to a decrease in toughness during manufacturing, an increase in costs, and a decrease in workability, the Co content is set to 0.50% or less, preferably 0.40% or less, and more preferably 0.30% or less.

[0039] <Mg:0.0001~0.0100%> Mg is an element added as a deoxidizing element. In addition, Mg contributes to improving manufacturability by refining ferrite grains, improving surface defects called ridging, and improving workability of welds. In order to obtain the effects of Mg, the Mg content is set to 0.0001% or more, preferably 0.0003% or more. However, excessive addition of Mg significantly reduces corrosion resistance and also leads to reduced workability due to coarse MgO, so the Mg content is set to 0.0100% or less, preferably 0.0080% or less, and more preferably 0.0050% or less.

[0040] <Sb:0.001~0.300%> Sb is an element that segregates at grain boundaries and has the effect of increasing high-temperature strength. In order to obtain the effect of Sb, the Sb content is set to 0.001% or more, preferably 0.005% or more. However, since excessive addition of Sb leads to grain boundary cracking during processing and cracking during welding due to the segregation of Sb, the Sb content is set to 0.300% or less, preferably 0.200% or less, and more preferably 0.100% or less.

[0041] <REM:0.001~0.500%> REM (rare earth elements) are elements effective in improving oxidation resistance. In order to obtain the effects of REM, the REM content is set to 0.001% or more, preferably 0.005% or more. However, even if REM is added in excess, the effect is saturated and REM sulfides lead to a decrease in corrosion resistance, so the REM content is set to 0.500% or less, preferably 0.400% or less, and more preferably 0.300% or less. REM follows the general definition. That is, REM refers to two elements, scandium (Sc) and yttrium (Y), and 15 elements (lanthanoids) from lanthanum (La) to lutetium (Lu). REM may be added alone or as a mixture.

[0042] <Ga:0.0001~0.3000%> Ga is an element effective in improving corrosion resistance and suppressing hydrogen embrittlement. To obtain the effects of Ga, the Ga content is set to 0.0001% or more, preferably 0.0005% or more. However, since excessive addition of Ga generates coarse sulfides and leads to a decrease in workability, the Ga content is set to 0.3000% or less, preferably 0.2000% or less, and more preferably 0.1000% or less.

[0043] <Ta:0.001~1.000%、Hf:0.001~1.000%> Ta and Hf are elements effective for improving high-temperature strength. In order to obtain the effects of Ta and Hf, the Ta content and Hf content are each set to 0.001% or more, preferably 0.005% or more. However, since excessive addition of Ta and Hf leads to an increase in manufacturing costs, the Ta content and Hf content are each set to 1.000% or less, preferably 0.800% or less, more preferably 0.500% or less.

[0044] <Bi:0.001~0.200%> Bi is an element effective in improving machinability. To obtain the effect of Bi, the Bi content is set to 0.001% or more, preferably 0.005% or more. However, since excessive addition of Bi leads to an increase in manufacturing costs, the Bi content is set to 0.200% or less, preferably 0.150% or less, and more preferably 0.100% or less.

[0045] The ferritic stainless steel sheet according to the embodiment of the present invention satisfies the following formula (1). 7.7×(C+N)≦Ti+Nb≦0.340 (1) In the formula, each element symbol represents the content (mass %) of each element. By setting Ti+Nb to 7.7×(C+N) or more, C and N can be fixed, so that the average Lankford value can be secured within a specified range, and cracks (α fracture) near the punch shoulder radius during deep drawing can be suppressed. Also, by setting Ti+Nb to 0.340 or less, inclusions such as carbonitrides and oxides can be reduced, and cracks (α fracture) near the punch shoulder radius during deep drawing can be suppressed.

[0046] The ferritic stainless steel sheet according to the embodiment of the present invention has an average Lankford value (hereinafter sometimes abbreviated as "average r-value") of 1.20 or more, preferably 1.25 or more, and more preferably 1.40 or more. By controlling the average r-value within such a range, cracks (α-fracture) near the punch shoulder radius during deep drawing can be suppressed. The upper limit of the average r-value is not particularly limited, but is typically 3.00 or less. Here, the average r-value is determined as follows. First, a tensile test piece according to JIS Z2241:2022, Appendix B, No. 13B is prepared from a ferritic stainless steel plate, and the dimensions and gauge length of the tensile test piece are measured. Next, the dimensions and gauge length of the tensile test piece after applying a 15% strain by a tensile test are measured, and the Lankford value in the rolling direction (r 0 ), the Lankford value at 45° to the rolling direction (r 45 ) and the Lankford value at 90° to the rolling direction (r 90 ) is calculated. Then, the average r value is calculated using the following formula: Average r value = (R 0 +2r 45 +r 90 ) / 4

[0047] The ferritic stainless steel sheet according to the embodiment of the present invention has a 0.2% yield strength of 200 to 290 MPa, preferably 210 to 285 MPa, and more preferably 220 to 260 MPa. In particular, by making the 0.2% yield strength 200 MPa or more, the occurrence of wall breaks due to a decrease in yield strength can be suppressed. Also, by making the 0.2% yield strength 290 MPa or less, vertical cracks at corners can be suppressed. Here, the 0.2% proof stress can be determined by preparing a No. 13B tensile test piece described in Appendix B of JIS Z2241:2022 from a ferritic stainless steel plate and conducting a tensile test in accordance with JIS Z2241:2022.

[0048] The ferritic stainless steel sheet according to the embodiment of the present invention has a surface arithmetic mean roughness Ra of 0.01 to 1.00 μm, preferably 0.05 to 0.90 μm, and more preferably 0.10 to 0.80 μm. In particular, by making the surface arithmetic mean roughness Ra 0.01 μm or more, the wettability of the lubricant oil can be ensured during deep drawing, making it easier to suppress various cracks. In addition, by making the surface arithmetic mean roughness Ra 1.00 μm or less, vertical cracks originating from surface irregularities can be suppressed. Here, the arithmetic mean roughness Ra of the surface can be measured in accordance with JIS B0601:2013.

[0049] The ferritic stainless steel sheet according to the embodiment of the present invention has a surface roughness Rz of 0.10 to 5.00 μm, preferably 0.15 to 4.80 μm, and more preferably 0.20 to 4.50 μm. In particular, by making the surface roughness Rz 0.10 μm or more, the wettability of the lubricant oil can be ensured during deep drawing, making it easier to suppress various cracks. In addition, by making the surface roughness Rz 5.00 μm or less, vertical cracks originating from the surface irregularities can be suppressed. The maximum height roughness Rz of the surface can be measured in accordance with JIS B0601:2013.

[0050] The ferritic stainless steel sheet according to the embodiment of the present invention has a ratio (Rz / Ra) of the maximum height roughness Rz of the surface to the arithmetic mean roughness Ra of the surface of 2.0 to 15.0, preferably 2.5 to 14.0, and more preferably 3.0 to 12.0. By controlling Rz / Ra within this range, vertical cracks can be stably suppressed.

[0051] The thickness of the ferritic stainless steel sheet according to the embodiment of the present invention is not particularly limited and may be appropriately set according to the characteristics of the product in which the ferritic stainless steel sheet is used. For example, in consideration of the weight reduction of the ferritic stainless steel sheet and the battery components formed therefrom, the thickness of the ferritic stainless steel sheet is preferably 1.00 mm or less. In consideration of the rigidity of the ferritic stainless steel sheet and the battery components formed therefrom, the thickness of the ferritic stainless steel sheet is more preferably 0.20 mm or more. In consideration of the fire resistance and cost of the ferritic stainless steel sheet and the battery components formed therefrom, the thickness of the ferritic stainless steel sheet is more preferably 0.2 to 0.8 mm. In consideration of the weldability of the ferritic stainless steel sheet and the battery components formed therefrom, the thickness of the ferritic stainless steel sheet is even more preferably 0.3 to 0.6 mm.

[0052] The ferritic stainless steel sheet according to the embodiment of the present invention has properties suitable for deep drawing (e.g., 0.2% proof stress) because the composition, average Lankford value, 0.2% proof stress, arithmetic mean roughness Ra and maximum height roughness Rz of the surface, and the ratio of Rz / Ra are controlled. Therefore, the ferritic stainless steel sheet according to the embodiment of the present invention has excellent deep drawing workability and can suppress the occurrence of various cracks, making it suitable for use in deep drawing. Therefore, the ferritic stainless steel sheet according to the embodiment of the present invention is suitable for use in the manufacture of battery parts used in lithium ion secondary batteries, in particular, square cases.

[0053] (2) Manufacturing method of ferritic stainless steel sheet for battery components The method for producing a ferritic stainless steel sheet according to the embodiment of the present invention is not particularly limited as long as it is a method capable of producing a ferritic stainless steel sheet having the above-mentioned characteristics. For example, a method for producing a ferritic stainless steel sheet according to an embodiment of the present invention includes the following hot rolling, cold rolling, annealing and temper rolling steps for a stainless steel having the above composition.

[0054] <Hot rolling process> The hot rolling step is a step in which the stainless steel having the above composition is hot-rolled by heating it to a heating temperature of 1100 to 1300°C for 30 to 240 minutes in an atmosphere containing 10 to 30 volume % water vapor. If hot rolling is not performed under these conditions, it becomes difficult to control the surface roughness (particularly Rz / Ra) of the ferritic stainless steel sheet within a predetermined range. The concentration of water vapor is preferably 12 to 28 volume %, the heating temperature is preferably 1120 to 1250°C, and the heating time is preferably 35 to 230 minutes. After the hot rolling, annealing and pickling may be carried out as necessary.

[0055] <Cold rolling process> The cold rolling step is a step of cold rolling the hot-rolled sheet obtained in the hot rolling step. The conditions of the cold rolling are not particularly limited and may be appropriately adjusted depending on the composition of the stainless steel.

[0056] <Annealing process> The annealing step is a step in which the cold-rolled sheet obtained in the cold rolling step is annealed at a final annealing temperature of 850 to 1050° C. If annealing is not performed under these conditions, it becomes difficult to control the average r-value and 0.2% proof stress of the ferritic stainless steel sheet within the specified range. The final annealing temperature is preferably 860 to 1000° C.

[0057] The temper rolling step is a step in which the annealed sheet obtained in the annealing step is temper rolled to an elongation rate of 0.03 to 1.00% under conditions that satisfy the following formula (2). -190≦50Cr+500Si-T+300A≦250 (2) In the formula, Cr and Si represent the Cr and Si contents (mass%), T represents the final annealing temperature (°C) in the annealing process, and A represents the elongation rate (%) in the temper rolling process. If the temper rolling is not performed under the above conditions, it becomes difficult to control one or more of the average r-value, 0.2% yield strength, and surface roughness (Ra, Rz, Rz / Ra) of the ferritic stainless steel sheet within the specified range. The elongation is preferably 0.04 to 0.80%, and the range of 50Cr+500Si-T+300A is preferably -180 to 240.

[0058] (3) Battery parts The battery component according to the embodiment of the present invention includes the above-mentioned deep-drawn product of ferritic stainless steel material. The above-mentioned deep-drawn product of ferritic stainless steel material has good quality as a deep-drawn product because the occurrence of various cracks is suppressed. Therefore, the battery component including this drawn product is highly reliable. In particular, when the battery component is a rectangular case for a lithium-ion secondary battery, the battery component has excellent protection performance for the lithium-ion secondary battery and resistance to thermal runaway when the lithium-ion secondary battery is subjected to an impact due to a collision accident or the like, compared to a conventional rectangular case made of aluminum. The battery parts are not limited to the rectangular case of a lithium ion secondary battery, but may be parts other than the rectangular case of a lithium ion secondary battery (for example, a battery pack, a battery module, a battery cover, etc.).

[0059] When the battery part is a prismatic case for a lithium ion secondary battery, a typical example of a deep drawn product is shown in Figures 1A and 1B. Figure 1A shows a top view of the deep drawn product, and Figure 1B shows a side view of the deep drawn product. The deep-drawn product is preferably a rectangular case having a shape in which height H / width W is greater than 2 and radius of curvature R / width W of the corner is less than 0.15. A rectangular case having such a shape can be suitably used as a rectangular case for a lithium-ion secondary battery. Although FIG. 1A shows an example in which the top view is rectangular, the top view may be square. When the top view is square, the width W is the same as the length L.

[0060] (4) Manufacturing method of battery components A method for producing a battery component according to an embodiment of the present invention includes deep drawing the above-mentioned ferritic stainless steel sheet. The ferritic stainless steel sheet is preferably processed into a rectangular case by deep drawing. The rectangular case preferably has a shape in which height H / width W is greater than 2 and the radius of curvature of the corners R / width W is less than 0.15. By forming the rectangular case into such a shape, it can be suitably used as a rectangular case for a lithium ion secondary battery.

[0061] The above-mentioned ferritic stainless steel sheet has excellent deep drawing workability, and therefore can suppress various cracks during deep drawing. Therefore, intermediate annealing is not required during the deep drawing process, and the sheet can be deep drawn into a desired shape. The deep drawing can be carried out in accordance with a method known in the art. EXAMPLES

[0062] The present invention will be described in detail below with reference to examples, but the present invention should not be construed as being limited to these. A ferritic stainless steel sheet was prepared according to the following procedure. Stainless steel having the composition shown in Tables 1A and 1B (the balance being Fe and impurities) was melted, heated under the conditions (steam concentration, heating temperature, and heating time) shown in Tables 2A and 2B, and hot-rolled to obtain a hot-rolled sheet having a thickness of 3.5 mm. The hot-rolled sheet was then cold-rolled to obtain a cold-rolled sheet having a thickness of 0.5 mm. The cold-rolled sheet was then annealed under the conditions (final annealing temperature) shown in Tables 2A and 2B to obtain an annealed sheet. The annealed sheet was then temper-rolled under the conditions (elongation, formula (2)) shown in Tables 2A and 2B.

[0063] [Table 1A]

[0064] [Table 1B]

[0065] [Table 2A]

[0066] [Table 2B]

[0067] The ferritic stainless steel sheets obtained above were subjected to the following evaluations.

[0068] <0.2% yield strength> Tensile test pieces according to No. 13B in Appendix B of JIS Z2241:2022 were prepared from ferritic stainless steel sheets, and tensile tests were carried out in accordance with JIS Z2241:2022.

[0069] <Average r value> A tensile test piece according to JIS Z2241:2022, Appendix B, No. 13B was prepared from the ferritic stainless steel plate, and the dimensions and gauge length of the tensile test piece were measured. Next, the dimensions and gauge length of the tensile test piece after applying a 15% strain by a tensile test were measured, and the Lankford value in the rolling direction (r0 ), the Lankford value at 45° to the rolling direction (r 45 ) and the Lankford value at 90° to the rolling direction (r 90 ) was obtained. The average r value was then calculated using the following formula: Average r value = (R 0 +2r 45 +r 90 ) / 4

[0070] <Ra、Rz、Rz / Ra> The arithmetic mean roughness Ra and maximum height roughness Rz of the surface of the ferritic stainless steel plate were measured using a contact type surface roughness meter (Surfcom 2800 manufactured by Tokyo Seimitsu Co., Ltd.) in accordance with JIS B0601:2013. In these measurements, the reference length was set to 4 mm. The measurements of Ra and Rz were performed at five arbitrary locations, and the average value was used as the measurement result. Rz / Ra was calculated based on the obtained Ra and Rz.

[0071] <Deep drawing processability> A rectangular case was made from a ferritic stainless steel plate according to the procedure shown in Figure 2, and various cracks were evaluated. Specifically, the ferritic stainless steel plate was cut into an elliptical shape (step (a)), and then deep-drawn into an elliptical cylindrical shape (step (b)). Next, two-stage deep-drawing was performed (steps (c) and (d)) to obtain a rectangular shape with a final height H of 100 mm, width W of 35 mm, length L of 170 mm, and a corner curvature radius R of 5 mm. In the evaluation of the drawing workability, those in which no cracks were observed were indicated by ⊚, those in which no cracks were observed but fine wrinkles were observed were indicated by ◯, and those in which cracks were observed were indicated by x. The results of the above evaluations are shown in Tables 3A and 3B.

[0072] [Table 3A]

[0073] [Table 3B]

[0074] As shown in Tables 3A and 3B, Test Nos. 1 to 17 (examples of the present invention) had composition, average Lankford value, 0.2% yield strength, Ra, Rz, and Rz / Ra ratio within the specified ranges, and therefore had no cracks and good deep drawability.

[0075] In contrast, in Test No. 18 (Comparative Example), the C content was too high, resulting in a low average r-value and the occurrence of cracks (α-fracture) in the vicinity of the punch shoulder radius. In Test No. 19 (Comparative Example), the N content was too high, so that the average r-value was low and cracks (α-fracture) occurred in the vicinity of the punch shoulder radius. In Test No. 20 (Comparative Example), the Si content was too high, resulting in a high 0.2 proof stress and the occurrence of vertical cracks at the corners. Test No. 21 (comparative example) did not contain Si, and therefore the 0.2% proof stress was low, and wall break occurred. In Test No. 22 (Comparative Example), the contents of Mn, P and S were too high, so that the 0.2 proof stress was high and vertical cracks occurred at the corners. In Test No. 23 (Comparative Example), the Cr content was too high, resulting in a high 0.2 proof stress and the occurrence of vertical cracks at the corners. In Test No. 24 (Comparative Example), the Cr content was too low, so the 0.2% proof stress was low and wall break occurred. In Test No. 25 (Comparative Example), the Ni content was too high, so the 0.2% proof stress was high and vertical cracks occurred at the corners.

[0076] Test No. 26 (comparative example) did not contain Ni, and therefore the 0.2% proof stress was low, and wall break occurred. In Test No. 27 (Comparative Example), the Cu content was too high, so the 0.2% proof stress was high and vertical cracks occurred at the corners. Test No. 28 (comparative example) did not contain Cu, and therefore the 0.2% proof stress was low, and wall break occurred. In Test No. 29 (Comparative Example), the Ti content was too high, and therefore cracks (α-fracture) occurred in the vicinity of the punch shoulder radius. In Test No. 30 (Comparative Example), the Ti content was too low, so the average r-value was low and cracks (α-fracture) occurred in the vicinity of the punch shoulder radius. In Test No. 31 (Comparative Example), the Nb content was too high, so that the average r-value was low and cracks (α-fracture) occurred in the vicinity of the punch shoulder radius. In Test No. 32 (Comparative Example), the Al content was too high, and therefore cracks (α-fracture) occurred in the vicinity of the punch shoulder radius. In Test No. 33 (Comparative Example), the Al content was too low, so that the average r-value was low and cracks (α-fracture) occurred in the vicinity of the punch shoulder radius. In Test No. 34 (Comparative Example), the Ti+Nb content exceeded 0.340 mass %, so that cracks (α fracture) occurred in the vicinity of the punch shoulder radius. In Test No. 35 (Comparative Example), the Ti+Nb content was less than 7.7 (C+N), so the average r-value was low and cracks (α-fracture) occurred in the vicinity of the punch shoulder radius.

[0077] In Test Nos. 36 and 37 (Comparative Examples), the water vapor concentration during heating in the hot rolling process was not within an appropriate range, so that Rz / Ra could not be controlled within a predetermined range, and vertical cracks occurred at the corners. In Test Nos. 38 and 39 (Comparative Examples), the heating temperature during heating in the hot rolling process was not within an appropriate range, so that Rz / Ra could not be controlled within a predetermined range, and vertical cracks occurred at the corners. In Test Nos. 40 and 41 (Comparative Examples), the heating time during heating in the hot rolling process was not within an appropriate range, so that Rz / Ra could not be controlled within a predetermined range, and vertical cracks occurred at the corners. In Test Nos. 42 and 43 (Comparative Examples), the water vapor concentration, heating temperature and heating time in the hot rolling process, and the elongation rate in the temper rolling process were not within the appropriate ranges, so Ra and Rz were large and vertical cracks occurred at the corners. In Test Nos. 44 to 46 (Comparative Examples), the elongation in the skin pass rolling process was not within an appropriate range, so that the 0.2% proof stress or Rz / Ra could not be controlled within a predetermined range, and vertical cracks occurred at the corners. In Test Nos. 47 and 48 (Comparative Examples), the final annealing temperature in the annealing process was not within the appropriate range, so the 0.2% proof stress or average r-value could not be controlled within the specified range, and vertical cracks occurred at the corners and cracks (α fracture) occurred near the punch shoulder radius. In Test Nos. 49 and 50 (Comparative Examples), the condition of formula (2) was not satisfied in the temper rolling process, and therefore the 0.2% yield strength, average r-value, or Rz / Ra could not be controlled within the specified range, and vertical cracks occurred at the corners and cracks (α-fracture) occurred near the punch shoulder radius.

[0078] As can be seen from the above results, the present invention can provide a ferritic stainless steel sheet for battery components that has excellent deep drawing workability and is capable of suppressing the occurrence of various cracks, and a manufacturing method thereof. In addition, the present invention can provide a highly reliable battery component and a manufacturing method thereof.

Claims

1. The alloy contains, on a mass basis, C: 0.001-0.020%, N: 0.001-0.020%, Si: 0.01-0.60%, Mn: 0.01-0.70%, P: 0.001-0.050%, S: 0.0001-0.0014%, Cr: 9.5-18.5%, Ni: 0.001-0.700%, Cu: 0.001-1.200%, Ti: 0.03-0.27%, Nb: 0.001-0.200%, Al: 0.003-0.180%, and the balance being Fe and impurities; an average Lankford value of 1.20 or more, a 0.2% yield strength of 200 to 290 MPa, an arithmetic mean roughness Ra of the surface of 0.01 to 1.00 μm, a maximum height roughness Rz of the surface of 0.10 to 5.00 μm, and a ratio Rz / Ra of the maximum height roughness Rz to the arithmetic mean roughness Ra of 2.0 to 15.0, A ferritic stainless steel sheet for battery components that satisfies the following formula (1): 7.7×(C+N)≦Ti+Nb≦0.340 (1) In the formula, each element symbol represents the content (mass %) of each element.

2. On a mass basis, Mo: 0.01 to 2.50%, V: 0.01 to 0.50%, Zr: 0.01 to 0.50%, B: 0.0001 to 0.0050%, Ca: 0.0001 to 0.0100%, W: 0.01 to 2.50%, Sn: 0.01 to 0.50%, Co: 0.01 to 0.50%, Mg: 0.0001 to 0.0100%, Sb: The ferritic stainless steel sheet for battery components according to claim 1, further comprising one or more selected from the group consisting of 0.001 to 0.300%, REM: 0.001 to 0.500%, Ga: 0.0001 to 0.3000%, Ta: 0.001 to 1.000%, Hf: 0.001 to 1.000%, and Bi: 0.001 to 0.200%.

3. On a mass basis, Si: 0.01 to 0.50%, Cr: 9.5% or more and less than 18.0%, Ti: 0.10% or more and less than 0.25%, Nb: 0.001% or more and less than 0.100%, 3. The ferritic stainless steel sheet for battery components according to claim 1, wherein the average Lankford value is 1.40 or more, the 0.2% yield strength is 220 to 260 MPa, and the ratio Rz / Ra is 3.0 to 12.

0.

4. The ferritic stainless steel sheet for battery components according to claim 1 or 2, having a thickness of 0.20 to 1.00 mm.

5. The ferritic stainless steel sheet for battery components according to claim 1 or 2, which is used for deep drawing.

6. 3. The ferritic stainless steel sheet for a battery component according to claim 1, wherein the battery component is a rectangular case for a lithium ion secondary battery.

7. a hot rolling process in which a stainless steel containing, by mass, 0.001-0.020% C, 0.001-0.020% N, 0.01-0.60% Si, 0.01-0.70% Mn, 0.001-0.050% P, 0.0001-0.0014% S, 9.5-18.5% Cr, 0.001-0.700% Ni, 0.001-1.200% Cu, 0.03-0.27% Ti, 0.001-0.200% Nb, 0.003-0.180% Al, with the balance being Fe and impurities, is heated to a heating temperature of 1100-1300° C. for 30-240 minutes in an atmosphere containing 10-30% by volume of water vapor, and hot rolled; a cold rolling step of cold rolling the hot-rolled sheet obtained in the hot rolling step; An annealing step of annealing the cold-rolled sheet obtained in the cold rolling step at a final annealing temperature of 850 to 1050 ° C.; a temper rolling process in which the annealed sheet obtained in the annealing process is temper rolled to an elongation rate of 0.03 to 1.00% under conditions that satisfy the following formula (2); A method for producing a ferritic stainless steel sheet for battery components, comprising: -190≦50Cr+500Si-T+300A≦250...(2) In the formula, Cr and Si represent the Cr and Si contents (mass%), T represents the final annealing temperature (°C) in the annealing step, and A represents the elongation rate (%) in the temper rolling step.

8. The stainless steel contains, by mass, 0.01 to 2.50% Mo, 0.01 to 0.50% V, 0.01 to 0.50% Zr, 0.0001 to 0.0050% B, 0.0001 to 0.0100% Ca, 0.01 to 2.50% W, 0.01 to 0.50% Sn, 0.01 to 0.50% Co, 0.01 to 0.50% Mg, 0.0001 to 0.0100% S The method for producing a ferritic stainless steel sheet for battery components according to claim 7, further comprising one or more selected from the group consisting of b: 0.001 to 0.300%, REM: 0.001 to 0.500%, Ga: 0.0001 to 0.3000%, Ta: 0.001 to 1.000%, Hf: 0.001 to 1.000%, and Bi: 0.001 to 0.200%.

9. The stainless steel has, by mass, Si: 0.01 to 0.50%, Cr: 9.5% or more and less than 18.0%, Ti: 0.10% or more and less than 0.25%, and Nb: 0.001% or more and less than 0.100%. The method for producing a ferritic stainless steel sheet for battery components according to claim 7 or 8.

10. A battery component comprising a deep-drawn product made of the ferritic stainless steel sheet for battery components according to claim 1 or 2.

11. The battery component according to claim 10, wherein the deep drawn product is a rectangular case having a shape in which height H / width W is greater than 2 and a radius of curvature R / width W of a corner portion is less than 0.

15.

12. A method for producing a battery component, comprising deep drawing the ferritic stainless steel sheet for battery components according to claim 1 or 2.

13. The method for producing a battery component according to claim 12, wherein the deep drawing process forms a rectangular case, and the rectangular case has a shape in which height H / width W is greater than 2 and a radius of curvature R / width W of a corner portion is less than 0.15.

Citation Information

Patent Citations

  • Method and apparatus for forming prismatic container made of ferritic stainless steel, and prismatic container

    JP2009113059A